Stable roles, changed skills: teacher candidate responses to instruction about adolescent psychosocial support practices. Issue 1 (2nd January 2017) - Phillippo, Kate; Blosser, Allison
Abstract: By virtue of their day-to-day contact with students, teachers are uniquely positioned to notice and respond to student psychosocial issues, both mental health problems and issues like peer harassment that can contribute to mental health problems. Yet, teachers' opportunities to learn about providing psychosocial support remain scattered. The present study investigates the impact of one teacher education program's efforts to promote productive teacher interactions with students experiencing psychosocial issues. The intervention – a six-week module that comprised part of a master's-level teacher education practicum support course – aimed to increase candidates' ability to recognize and respond to student psychosocial issues in the classroom. This study's pre-test/post-test design asked 72 candidates to respond to vignettes portraying situations of student psychosocial distress, and also gauged candidates' preference for working with populations experiencing psychosocial distress. Pre- to posttest change was gauged first with a rubric and then compared using Wilcoxon signed-rank tests. While candidates' sense of their preferred role responsibilities regarding work with students experiencing psychosocial distress did not change, their demonstrated knowledge and practice skills in specific areas related to student psychosocial issues, particularly consultation and referral, did. Implications for teacher education regarding student support needs, and school-based mental health practice that engages teachers, are discussed.